2016
DOI: 10.1111/jzo.12399
|View full text |Cite
|
Sign up to set email alerts
|

Population genetic structure of the urban fox in Sapporo, northern Japan

Abstract: In some countries, the red fox Vulpes vulpes has been rapidly expanding its range into urban and suburban areas, where it is referred to as the 'urban fox'. In the city of Sapporo, northern Japan, the population of urban foxes has been increasing since the 1990s. Because the red fox carries several zoonoses, it is important to understand its population structure and migration status in urban areas, for not only basic biology but also public health. In this study, to clarify population genetic structure and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Habitat suitability patterns of foxes in Greater London show a clear distinction from hedgehogs, with highest suitability in the urban centre. This pattern is also observed in other cities in the United Kingdom, Italy, Australia, Switzerland and Japan, where foxes were found throughout urban areas, including the centre (Harris & Trewhella 1988, Cignini & Riga 1997, Marks & Bloomfield 1999, Gloor et al 2001, Kato et al 2017. Similarly, grey squirrels also have the highest habitat suitability in the centre of Greater London, but the hotspot is much smaller than that of foxes.…”
Section: Habitat Suitability Mapping and Urbanisation Potentialsupporting
confidence: 59%
See 1 more Smart Citation
“…Habitat suitability patterns of foxes in Greater London show a clear distinction from hedgehogs, with highest suitability in the urban centre. This pattern is also observed in other cities in the United Kingdom, Italy, Australia, Switzerland and Japan, where foxes were found throughout urban areas, including the centre (Harris & Trewhella 1988, Cignini & Riga 1997, Marks & Bloomfield 1999, Gloor et al 2001, Kato et al 2017. Similarly, grey squirrels also have the highest habitat suitability in the centre of Greater London, but the hotspot is much smaller than that of foxes.…”
Section: Habitat Suitability Mapping and Urbanisation Potentialsupporting
confidence: 59%
“…2001, Kato et al. 2017). Similarly, grey squirrels also have the highest habitat suitability in the centre of Greater London, but the hotspot is much smaller than that of foxes.…”
Section: Discussionmentioning
confidence: 99%
“…Foxes in Japan demonstrate the adaptability to food resources that would be expected given their success as a globally widespread mesopredator. This adaptability has meant that foxes have been able to colonize urban areas (Andrewartha et al, 2021; Harris & Rayner, 1986; Ikeda et al, 2014; Kato et al, 2017; Parsons et al, 2020; Stepkovitch et al, 2019; Tsukada et al, 2000; Uraguchi et al, 2009; Walter et al, 2018). It has also meant that foxes have been incredibly successful as exotic pest species, becoming one of the primary causes of devastating mammal species declines and losses in Australia (Fairfax, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Previous molecular studies on colonization of urban habitats by the red fox showed that the process starts usually from a few locations near the city borders and spreads gradually into its central parts 60 , 61 . The red fox movements through the city can be affected by human-made infrastructures 62 , like railways 63 , roads 62 , 64 , 65 . Densely built-up areas are usually avoided by foxes 14 , 62 , while specific migration corridors like roadside or railway vegetation 62 , 66 will facilitate the process.…”
Section: Discussionmentioning
confidence: 99%